KONSELING DENGAN PENDEKATAN RATIONAL EMOTIVE BEHAVIOR THERAPY UNTUK MENGATASI KEBIASAAN MEROKOK - Rina Lestari (Fakultas Tarbiyah dan Ilmu Keguruan Institut Agama Islam Negeri Kerinci, 2018)
Smoking is an act of waste and waste on property. The purpose of this study were to described: 1) smoking habits of students before giving Rational Emotive therapy? ; 2) student smoking habits after giving Rational Emotive therapy ?; and 3) the effectiveness of Rational Emotive counseling therapy in reducing students' smoking habits. This research was used pre test & post test design. The population in this research were all class X students of SMAN 3 Pekanbaru who had smoking habits with totaling 32 students. To determine the sample of this study, the researcher used purposive sampling. Then, through this technique, 5 students were used as the research sample. Besides, the data was analysed by using